Renal osteodystrophy in a sample of patients on dialysis in Northeastern Brazil: a cross-sectional analysis - Luiz Alberto Soares de Araújo Coutinho; Ana Paula Santana Gueiros; Júlia Braga Vaz; Eduarda Cerqueira Russo; Vanda Jorgetti; José Edevanilson de Barros Gueiros (Brazilian Journal of Nephrology)
Abstract Introduction: Mineral and bone meta-bolism disorders in chronic kidney disease (CKD-MBD) are one of the most significant complications of CKD. The objective of this study was to describe the types of renal osteodystrophy (ROD) and the clinical and osteometabolic profiles of dialysis patients undergoing bone biopsy in Pernambuco. Methods: A cross-sectional, retrospective study that assessed patients biopsied between January 2004 and September 2021 was conducted. Patients receiving conservative treatment for CKD, kidney transplant recipients, and those with inadequate biopsies were excluded. All clinical and laboratory parameters were from the time of biopsy. Results: We assessed 250 patients with median age of 48 years (57.6% women) and on dialysis for a median time of 108 months. Regarding the diagnosis of ROD, the prevalence was: osteitis fibrosa (54.5%), mixed disease (30.4%), adynamic bone disease (12.4%), and osteomalacia (3.2%). The prevalences of osteoporosis, aluminum toxicity, and iron toxicity were 43.6%, 46.8% and 27.5%, respectively. Conclusions: We demonstrated a high prevalence of diseases related to high bone turnover and aluminum toxicity.